Reconstructing Erpenius' Library : The First Collection of Oriental Manuscripts at Cambridge University Library - Daneshgar, Majid, (Islamic Manuscripts and Books., 2024)
This volume is the first comprehensive study of one of the most important collections of oriental manuscripts in early modern Europe which belonged to Thomas Erpenius (d. 1624), the renowned Dutch Arabist, orientalist and the first Chair of Arabic Studies at Leiden University. It reconstructs his personal library which was the center of scholarly debates for centuries, full of rare and sometimes unique materials. Widely known as a rich source of Muslim literature and Asian languages, the collection was purchased by George Villiers, the 1st Duke of Buckingham (d. 1628) and ultimately donated by his widow, Katherine Villiers, to Cambridge University Library in June 1632. This volume provides detail on Erpenius' life and career, his manuscript collections and their reception and preservation in Cambridge. Furthermore, the author challenges the idea of European orientalism by redefining the role of Erpenius in in shaping academic study of the Orient and 'organic' orientalism in the West.